A wide stopband multilayer substrate integrated waveguide bandpass filter with suppression of higher-order mode coupling. Issue 10 (2nd December 2021) - Tang, Cong; Cheng, Fei; Gu, Chao
Abstract: This paper presents a compact multilayer substrate integrated waveguide (SIW) bandpass filter with wide stopband. The square SIW cavity resonators in multilayer substrates are horizontally and vertically coupled with magnetic coupling. By properly designing the coupling structure, the couplings between the higher-order resonant modes can be suppressed. Compared with the conventional single-layer SIW filters, the proposed multilayer SIW filter also exhibits a compact size. To verify the design concept, a double-layered SIW filter is fabricated and measured. The measured results agree well with the simulations. The measured results show that the upper stopband of the filter is extended to 2.73 times of the center frequency 8.02 GHz.